Transglutaminase-catalyzed modification of fish skin gelatin enhanced the protection of microcapsules to Limosilactobacillus reuteri. (December 2022) - Zhang, Yulong; Guo, Shuailing; Fu, Guiming; Chen, Yanru; Wan, Yin; Wu, Xiaodan; Xu, Ziwen; Liu, Jingjing; Xie, Zijun
Abstract: In the present study, the tilapia skin gelatin was modified with Transglutaminase (TGase) to obtain wall materials with good film-forming performance. The effects of different fish skin gelatin cross-linking degree on the physical and chemical properties of the wall material solution were compared. When the fish skin gelatin cross-linking degree was 15.45%, the wall material solution had the highest emulsification, emulsification stability, foaming ability and foam stability, which were 4.25 m 2 /g, 63.27 min, 140.00% and 32.14%, respectively. Therefore, the wall material with 15.45% fish skin gelatin cross-linking degree was used for spray drying to prepare Limosilactobacillus reuteri microcapsules. The particle size of the microcapsules was 40.5 μm, the moisture content was 3.93%, the microcapsules had good storage stability at 4 °C, and the expected shelf life was 28 days. The survival rate of L. reuteri in simulated gastrointestinal fluid increased by 43.94%, It was indicated that microcapsules with fish skin gelatin modified by TGase had the strong gastric acid resistance and could release more live bacteria in the gastrointestinal tract. The results can provide guidance for the large-scale production of L. reuteri -loaded microcapsules and the application of probiotics in food. Graphical abstract: Image 1 Highlights: TGase modified improved the film-forming property of fish skin gelatin for the wall material of microcapsules. Microcapsules with fish skin gelatin modified by TGase can improve the survival rate of L. reuteri. Microcapsules with fish skin gelatin modified by TGase have strong storage properties of L. reuteri .